Pengembangan Arsitektur Model Proses Bisnis Pada Pondok Pesantren - Lestari, Eka Puji Rahayu; Titania, Hagar Prily; Dewi, Anis Shiva ‘Ulia; Yaqin, Muhammad Ainul (STIKOM Tunas Bangsa Pematangsiantar, 2020)
Islamic boarding school is a religious education institution that teaches and practices Islamic religious education therein. Modeling of Islamic boarding school business processes is a clear and structured description of the flow of activities/business processes in every action that will be taken on activities in boarding schools. Data analysis uses the Porter Value Chain technique to identify the division of main business processes and supporting business processes, while the technique in modeling business processes is to use BPMN (Business Process Modeling & Notation) based on SOP (Standard Operating Procedure) of each existing business process/activity. The final results obtained from this research are in the form of an architecture of the business process model of Islamic boarding school that can be used as a reference in conducting every business process/activity in Islamic boarding school. So that with this business process architecture model, the implementation of activities can be structured and run in accordance with the expected goals, and can improve the quality of Islamic boarding schools.